Penerapan metode Jibril: progam pembelajaran Al-Qur’an untuk peningkatan bacaan siswa SMP Islam Sabilurrosyad Malang - Afifah, Fiqi Ummayatul (Maliki Interdisciplinary Journal, 2023)
The method is a step or way to do something so that something can be achieved. In the teaching and learning process of the Qur’an at Sabilurrosyad Middle School, the Jibril method is used which is talqin-taqlid (the teacher gives an example and then the students imitate). The method is motivated by the command of Allah SWT to the Prophet Muhammad to follow the recitation of the Qur’an which was recited by the angel Gabriel. This study aims to describe the learning methods used in improving students’ reading. In this study, researchers used a descriptive qualitative approach paradigm. The results of the study include several things: 1) learning the Jibril method for increasing reading is carried out using the talqin-taqlid method. 2) the target quality of learning is based on an assessment that includes tajwid (theory and practice), fashohah and ghorib and musykilat. 3) learning scenarios include opening, talqin-ittiba’, urdhoh, review, reading deposit and closing with direction and motivation given by the teacher to students